PP.10 CRL Discordance and Adverse Perinatal Outcome in Twins the Stork Multiple Pregnancy Cohort. (26th April 2013) - D'Antonio, F; Khalil, A; Dias, T; Bhide, A; Thilaganathan, B
Abstract : Background: The role of first trimester ultrasound in predicting the outcome in twin pregnancies is conflicting. The aim of this study is to determine the association between crown-rump length (CRL) discordance and adverse perinatal outcome in twin pregnancies. Methodology: CRL discordance was related to early fetal loss <20, <24 weeks, perinatal mortality, birth weight (BW) and ultrasound estimated fetal weight (USS EFW) discordance ≥25%, intrauterine growth restriction (IUGR) and preterm birth <34 weeks of gestation. ROC and logistic regression analysis was performed to evaluate the importance CRL discordance in determining adverse perinatal outcome. Results: A total of 2, 155 twin pregnancies [420 monochorionic (MC) and 1, 735 dichorionic (DC)] were included in the study. CRL discordance had very poor prediction for fetal loss <20 (AUC of 0.61), < 24 weeks (AUC: 0.54), perinatal mortality (AUC of 0.52), BW discordance (AUC of 0.61), BW < 5th centile (AUC of 0.56), USS EFW discordance (AUC of 0.55) and preterm birth (AUC of 0.50). Overall mortality was significantly higher (p = 0.016) in MC (21/420) compared to DC (45/1735) twins. Logistic regression analysis demonstrated that chorionicity (p = 0.033 OR: 2.09, 95% C.I. from 1.06 to 4.010) independently contribute in determining mortality while CRL discordance (p = 0.201) did not. After adjusting for chorionicity, CRL discrepancy did not improve the detection of adverse outcome in either MC or DC twin pregnancies. Conclusion: CRL discordance is of poor predictive value for adverse perinatal outcomeafter 14 weeks of gestation in either MC or DC twin pregnancies.